ANALISIS REALISASI PENANAMAN MODAL ASING SEBELUM DAN SAAT TERJADINYA PANDEMI COVID-19 DI JAWA TIMUR - Nadia, Meria Ulva (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.01.TAHUN. 2021, 2021)
ABSTRACT Foreign investment in east java province has increased from 2011 to 2013. In 2011, foreign investment amounted to US$ 1312 million, in 2012 it was US$ 2298,9 million. Meanwhile, for 2013 it reached US$ 3396,3 million. However, when Indonesia was hit by the Covid-19 pandemic which had a negative impact on the Indonesian economy and various other sectors. So this study aims to analyze the differences in the realization of foreign investment before and during the Covid-19 pandemic in East Java. The population and sample in this study are the realization of foreign investment. The sample is the realization of foreign investment in East Java. The data used is secondary data obtained from the investment coordinating board. The statistical test used to test the hypothesis is paired sample t-test. The results of this study are that there are differences in the realization of foreign investment before and during the Covid-19 pandemic in East Java. Despite the Covid-19 pandemic in Indonesia, the realization of foreign investment in East Java has increased compared to before the Covid-19 pandemic, namely in the first to third quarters of 2019. Keywords: Covid-19 event study, investment, foreign investment.